Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00455-007-9128-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Radiation Effects on Tongue Function for Patients with Nasopharyngeal Carcinoma: A Preliminary Study

Abstract: The purpose of this study was to investigate early radiation effects on tongue function for patients with nasopharyngeal carcinoma (NPC) and to provide a scientific database for early intervention plans. Twelve subjects with NPC and 12 age- and sex-matched normal subjects were included. Tongue maximum isometric strength and endurance at 50% of maximum strength were obtained once from normal subjects with the Iowa Oral Performance Instrument (IOPI) and twice from the NPC subjects: before and 2 months after radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…Only one study [20] reported inter-rater reliability for tongue endurance, with a perfect correlation (r ¼ 1) between assessors [20]. Nine studies have reported test-retest reliability of tongue strength [11][12][13][14][16][17][18]21,22]. Robin et al [5] provided the first report describing the test-retest variability as low (implying reliability was high) based on the small size of an individual participant's standard deviations.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Only one study [20] reported inter-rater reliability for tongue endurance, with a perfect correlation (r ¼ 1) between assessors [20]. Nine studies have reported test-retest reliability of tongue strength [11][12][13][14][16][17][18]21,22]. Robin et al [5] provided the first report describing the test-retest variability as low (implying reliability was high) based on the small size of an individual participant's standard deviations.…”
Section: Introductionmentioning
confidence: 98%
“…Robin et al [5] provided the first report describing the test-retest variability as low (implying reliability was high) based on the small size of an individual participant's standard deviations. Subsequent studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23] reported strong correlations as measures of test-retest reliability with correlation coefficients ranging from r ¼ 0.76 to r ¼ 0.99. Only one study [22] reported tongue endurance test-retest reliability (r ¼ 0.99).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, several studies have demonstrated that neither tongue strength nor endurance measures were significantly different from pre- to post-treatment [1517]. However, one of these studies also reported lower tongue strength as compared with a healthy cohort [15].…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation of this area may cause numerous delayed complications, including dysphagia. The mechanism underlying this dysfunction is usually attributed to radiation-induced cranial nerve paralysis [8], but very little is known of the exact etiology since the number of long-term survivors is not large. The degenerative effects of RT on the hypoglossal nerve cause progressive wasting of the lingual muscles leading to a deficiency in protrusion and lateralization of tongue.…”
Section: Discussionmentioning
confidence: 99%